Primary Pelvic Hydatid Cyst: a Rare Case - Subedi, Kirtipal; Vaidhya, Karishma; Shrestha, Bigya; KC, Kamana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Hydatid cyst is ecchinococcal disease caused by tapeworm echinococcus, most commonly by metacestode stage of echinococcus granulosus. Liver is the most common organ to be aff ected followed by lungs and spleen. Primary hydatid cyst in the pelvis is rare. We report a case of primary isolated pelvic hydatid cyst diagnosed incidentally during laparotomy performed for adnexal mass. Key words: adnexae, albendazole, echinococcus, hydatid cyst, laparotomy